The Age of Consent : Young People, Sexual Abuse and Agency - Gleeson, Kate; Lumby, Catharine (University of New South Wales Press : UWA Publishing, 2019)
This book challenges received mainstream and scholarly ideas about how and why child abuse occurs and offers fresh ideas about understanding how we can enhance young people's agency and can make a difference to their lives by ensuring they have an opportunity to grow up developing their own voices and identities, free from adult coercion. The purpose of this edited collection is to bring interdisciplinary research around the high profile subject of child sexual abuse and look closely at why public concern and awareness is often diverted away from the real issues at stake. It challenges the noti.